The Role of Preventive Nursing Interventions in Reducing Treatment-Related Complications in Ovarian Cancer Patients: A Retrospective Cohort Study - Zhang J; Liu Q (International Journal of Women's Health)
Jing Zhang,1 Qiugui Liu2 1Department of Gynaecology and Obstetrics, Tangdu Hospital, Fourth Military Medical University, Xi’an, 710038, People’s Republic of China; 2Department of Oncology, Tangdu Hospital, Fourth Military Medical University, Xi’an, 710038, People’s Republic of ChinaCorrespondence: Qiugui Liu, Department of Oncology, Tangdu Hospital, Fourth Military Medical University, Xi’an, 710038, People’s Republic of China, Email tdguizi@163.comObjective: To evaluate the effectiveness of preventive nursing interventions in reducing treatment-related complications among patients with ovarian cancer.Setting: Retrospective cohort study.Participants: A total of 251 female patients with ovarian cancer were included. They were assigned to either a control group (n=134), receiving standard nursing care, or an observation group (n=117), receiving additional preventive nursing interventions.Interventions: The control group received standard nursing care, including routine health education, pharmacological symptom control, and vital sign monitoring.Primary and Secondary Outcome Measures: The primary outcome was the incidence of treatment-related complications. Secondary outcomes included the severity of nausea and vomiting, quality of life, psychological condition, and nursing satisfaction.Results: The observation group demonstrated a significantly lower incidence of treatment-related complications compared to the control group (P=0.001). Notable reductions in nausea, vomiting, and neuropathy were observed (P=0.015, P=0.035). Both groups showed improvements in psychological conditions post-intervention (P< 0.001); however, improvements were more significant in the observation group for depression and quality of life (P=0.004, P=0.007). Nursing satisfaction was also significantly higher in the observation group (P< 0.0001). Multivariate logistic regression revealed that preventive nursing interventions significantly reduced complication risks (OR=0.391, 95% CI: 0.228– 0.670, P =0.001), and treatment with carboplatin and paclitaxel was significantly related to increased complication risks.Conclusion: Preventive nursing interventions effectively reduce treatment-related complications and enhance clinical and psychological outcomes in patients undergoing ovarian cancer chemotherapy. These findings underscore the importance of personalized, proactive nursing care in oncology settings.Keywords: ovarian cancer, preventive nursing, treatment-related complications, quality of life, retrospective study